Analisis Tindak Tutur Representatif dalam Video Bertema “Sumber Energi Kelas 10 Kurikulum Merdeka” pada Channel Youtube Pura-pura Tau Fisika - Fadilla Ahammi; Muchammad Akbar Ibrani; Rika Ardiana Yuni Cahyaningrum; Anugrah Bintang; Alifia Diva Juniar; Asep Purwo Yudi Utomo; Qurrota Ayu Neina; Annisa Tetty Maharani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Speech act is one of the elements or components of pragmatics that involves speakers and listeners. Speech acts are classified into 5 major groups, including: representative speech acts (assertive speech acts), commissive speech acts, directive speech acts, expressive speech acts, declarative speech acts. In this research, we will only discuss one type of speech act, namely representative speech act. Representative speech acts are speech acts that describe a situation, convey knowledge, or information to speech partners. Representative speech acts are not only found in direct speech. However, you can also find it on social media accounts such as YouTube. The purpose of this research is to find out the typical speech acts in some YouTube playlist videos of the Physics channel Pura-Pura Tau. One of them is in a video entitled “Nonrenewable Energy Class 10 Independent Curriculum Definition, Sources, Examples and Benefits”. The method that researchers use is descriptive qualitative. The data collection technique in this article uses the listening technique which consists of two techniques, namely the free listening technique and the note technique. The results of this study are in the form of speech acts of telling, suggesting, stating, explaining. This research will help readers interpret and understand representative speech acts from various utterances spoken in social life.